Exploring the Occupational Physical Activity Levels in young Adult Restaurant Servers. - K. Doyle-Baker, Patricia; E. Wray, Heather (International Journal of Nutrition, 2019)
Physical activity (PA) decreases in late adolescence and young adulthood when this age cohort enters the workforce with many being employed in the foodservice industry. Daily energy expenditure can be divided between occupational physical activity (OPA) and leisure-time physical activity (LTPA). Although LTPA is known to be associated with positive health benefits, a limited number of studies have investigated the influence of OPA on LTPA in young restaurant servers. This study measured via accelerometry, OPA and LTPA for a 7-day period from a sample of young adult servers (n = 7, 23-29 years old) from two restaurants. Resting metabolic rate was measured via indirect calorimetry and inputted into the AMP 331 accelerometer for energy expenditure calculations. Energy expenditure patterns were compared to age- and sex-specific normative data, occupational classifications, and the Canadian PA Guidelines to Healthy Active Living (CPAG). Energy expenditure results and step count values were higher for working versus non-working days and working versus non-working periods. Daily, working energy expenditure was approximately equal to normative data, while non-working daily energy expenditure was lower. The working period energy expenditure placed this population in the ‘exceptionally active’ OPA classification. Minimum PA levels, based on CPAG were met each day, however 10,000-steps-per-day were only achieved on working days. None of the participants logged LTPA and therefore 100% of their PA came from OPA. More research is needed over a longer duration and at different times in the year to identify the effect OPA has on LTPA in this population.
Keywords: Occupational physical activity; leisure time physical activity; restaurant servers